The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/bcp.13821
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of artemether‐lumefantrine influence on nevirapine disposition: Clinically significant drug–drug interaction?

Abstract: AIMSIn this study the influence of first-line antimalarial drug artemether-lumefantrine on the pharmacokinetics of the antiretroviral drug nevirapine was investigated in the context of selected single nucleotide polymorphisms (SNPs) in a cohort of adult HIV-infected Nigerian patients. METHODSThis was a two-period, single sequence crossover study. In stage 1, 150 HIV-infected patients receiving nevirapine-based antiretroviral regimens were enrolled and genotyped for seven SNPs. Sparse pharmacokinetic sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…Abbreviations: n, sample size; C max , maximum concentration; T max , time to reach C max ; AUC 0 -336 , area under the concentration time curve from 0 to 336 h; AUC 0 -∞ , AUC curve extrapolated to infinity; t 1/2 , terminal phase half-life; CL/F, oral clearance; day 6 (C day 6 ) and day 10 (C day 10 ) plasma concentrations. influenced by CYP2B6 polymorphisms (14,20,36). The overall 30% higher exposure to lumefantrine when not stratified to CYP2B6 c.516GϾT genotypes is consistent with data from previous similar parallel design studies (29,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Abbreviations: n, sample size; C max , maximum concentration; T max , time to reach C max ; AUC 0 -336 , area under the concentration time curve from 0 to 336 h; AUC 0 -∞ , AUC curve extrapolated to infinity; t 1/2 , terminal phase half-life; CL/F, oral clearance; day 6 (C day 6 ) and day 10 (C day 10 ) plasma concentrations. influenced by CYP2B6 polymorphisms (14,20,36). The overall 30% higher exposure to lumefantrine when not stratified to CYP2B6 c.516GϾT genotypes is consistent with data from previous similar parallel design studies (29,(32)(33)(34).…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study showed that nevirapine-based ART phenotypically reduced artemether exposure with a corresponding rise in dihydroartemisinin exposure, as against the genotype-predicted rise in artemether and the reduction in dihydroartemisinin exposures in the absence of nevirapine, in CYP2B6 c.516TT subjects. In addition, although CYP2B6 is not the main enzyme responsible for the biotransformation of lumefantrine (10), the higher exposure to nevirapine of TT patients observed in our previously reported study (36) culminated in greater exposure to lumefantrine compared to their GG counterparts. Therefore, coadministration of nevirapine with artemether-lumefantrine favored higher exposures to the two principal determinants of antimalarial efficacy as dihydroartemisinin and lumefantrine exposures were approximately 4 and 46%, respectively, higher in TT than in GG patients (Tables 2 and 4).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…32 The patients were from a cohort of 150 HIV-infected patients previously genotyped and with measured plasma nevirapine levels. 30,33 The inclusion criteria were HIVpositive patients above 18 years of age on nevirapinebased ART combinations (of zidovudine + lamivudine or tenofovir + lamivudine or abacavir + lamivudine) with records of absolute lymphocyte count and CD4+ T lymphocyte counts over a period of at least a year. Patients with recent history of poor compliance according to pharmacy ART refill record were excluded.…”
Section: Data Of 139 Adult Hiv Seropositive Patients Attendingmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] However, only a limited number of studies have reported influence of both genotypes on CD4+ T lymphocytes counts and HIV RNA levels. 25,27,28 We previously reported influence of composite CYP2B6*6/*18 genotype on the pharmacokinetics of nevirapine in the presence of artemether-lumefantrine in a subgroup of 30 HIV-infected patients 30 The present retrospective study evaluates the influence of composite CYP2B6*6/*18 genotype on the trough plasma nevirapine (the concentration immediately before the next dose is administered), and HIV RNA (virologic response) levels as well as on the absolute lymphocyte and CD4+ T lymphocyte counts (immunologic responses) in genetically defined groups of HIV-infected adult Nigerian patients on nevirapine-based ART combinations.…”
Section: Introductionmentioning
confidence: 99%